Patient satisfaction in the emergency department an empirical investigation into its measurement, antecedents, and consequences - Abidova, Alina (2022)
ABSTRACT - The main purpose of this research is to investigate the relationships between patient satisfaction, its antecedents (including global perceptions, perceived quality dimensions, and expectations), and its impact on consequences (including confidence/trust, payment perception, and complaints), as well as defining and testing a conceptual model for patient satisfaction and related constructs in the context of an emergency department (ED). The key focus of this study is thus to define key factors promoting patient satisfaction in the ED which, in turn, influence a set of performance factors (such as payment perception, confidence/trust, and complaints) that can be used for improved resource allocation and the definition of priorities by hospital and health system managers. A further focus of the study is the investigation of the potential moderating effect of a set of controlling factors (including specific patients’ characteristics, psychological state, social and demographic attributes, and the state of health/health status) on the relationships between patient satisfaction, its antecedents, and consequences. First, an exploratory phase of research was necessary in order to examine the nature of EDs and identify the major gaps that could be addressed in the quantitative phase of research. Thus, after finishing the analysis of the qualitative phase of research, we proceeded develop the questionnaire. As a solid base for our conceptual model and the questionnaire, we considered the methodology used in the Indice Nacional de Satisfação do Cliente (ECSI–Portugal), which is based on structural equation modelling (SEM) with latent variables, along with the American Customer Satisfaction Index (ACSI) model, which consists of indices for drivers or causes of satisfaction (antecedents), satisfaction, and outcomes of satisfaction (consequences) with cause-and-effect relationships. In developing the questionnaire, we also took into account and reviewed the Instrumentos de Avaliação da Qualidade Hospitalar – Urgências Adultos (IAQH-UA), the fourth National Health Interview Survey (Inquérito Nacional de Saúde), as well as the survey used to investigate aging processes in Portugal. Our questionnaire was adapted, and other questions were added that enabled us to identify important issues according to our conceptual model. The appropriateness of the questionnaire was tested by administering the instrument to a small subset of the study’s population by launching a pilot survey with 20 interviewees. The investigation period for the study was January 1 through December 31, 2016. Data collection was performed from May 18, 2017 through November 30, 2017 and took place in the public hospital under investigation in Lisbon, Portugal. We chose the sample distribution with a 5% margin of error and a 95% confidence interval. The total sample size was 382 patients. The questionnaire was sent either by mail or e-mail, depending on the respondent’s preference. The data analysis included several steps: descriptive statistics; correlation coefficients; ANOVA and T-test; multiple regression analysis; stepwise multiple linear regression analysis; and SEM (path analysis). Our results reveal that meeting expectations and the overall satisfaction with doctors are the main patient satisfaction antecedents that primarily contribute to understanding the level of confidence/trust in the ED and that influence it as the main patient satisfaction consequence, both directly and indirectly. Even though there are more variables that influence confidence/trust in the ED through the perceived quality of healthcare rather than through satisfaction, we observe the strongest contribution in the mediation model through satisfaction, which shows its dominant role over the perceived quality of healthcare. In turn, controlling factors do not have a strong, significant impact on the relationship between patient satisfaction, its antecedents, and consequences. In our mediation model, we reveal that overall satisfaction with doctors can better explain confidence/trust in the ED through perceived quality of healthcare; however, meeting expectations can better explain confidence/trust in the ED through satisfaction. Trust and expectations play an important role in the doctor-patient relationship. Several researchers have noted that trust was more complex than expectations, as the older adults could be satisfied but not trust providers, or they could trust providers but not be satisfied. Other researchers have also emphasised the fact that patients may be satisfied with the visit but may not have a sense of trust and vice versa. In our research, we considered confidence/trust to be an outcome; thus, our results showed that a certain set of variables (overall satisfaction with doctors and meeting expectations) can bypass satisfaction and perceived quality of healthcare and have a direct influence on confidence/trust, while other sets of variables (qualitative perceived waiting time for triage and information about possible delays) cannot bypass satisfaction; still others (qualitative perceived waiting time to be called back by the doctor after the examinations and/or tests, privacy, and accessibility and availability) cannot bypass perceived quality of healthcare without any chance of direct influence on confidence/trust. By conceptualising patient satisfaction in the ED context based on our results, we may say that the perceived quality of healthcare and satisfaction are integral to each other. Further, satisfaction and perceived quality of healthcare play an important but distinct mediating role in strengthening the effect of patient satisfaction antecedents on patient satisfaction consequences, where the strongest patient satisfaction antecedents (the overall level of satisfaction with doctors and meeting patients’ expectations) and the main patient satisfaction consequence (confidence/trust in the ED) form a connecting link between two concepts (satisfaction and the perceived quality of healthcare). Hence, this analysis demonstrates the complexity of the research topic under discussion and the importance of investigating it further.